From general training to projectization implications for learning process and the role of business. - Taylor, Harry (1995)
"A large component of development aid in the past has been in the form of scholarships for oficials and managers to attend short and long training programmes in the west. However, it has increasingly been felt that the impact of such programmes is limited, and hence the donor community is placing increased emphasis on `projectized' training programmes, i.e. training that is geared to specific development projects in a particular country. This shift has implications for the nature of the training, the learning processes involved and the roles of trainers. This article explores these issues, firstly reviewing the debate between `open' and `projectized' training, and then going on to report on a case study involving a `projectized' learning event run for the Nigerian Civil Service as part of its Civil Service reform programame. The case study explores the main differences between `open' and `projectized' training, demonstrates some of the potential problems with `projectized' learning and, where appropriate, suggests solutions and offers a number of practical suggestions for trainers to consider for operating in an increasingly `projectized' training scene"
Keywords: Civil service - Training of; Civil service - Nigeria; Civil service